THE IMPACT OF MANAGEMENT - VAAS, Monica (My University, 2011)
Keeping employee turnover below target remains one of the most challenging issues facing modern day organisations. Whilst organisations look at various strategies to address the turnover challenge, the role of the manager/supervisor on employee turnover and retention remains one of the most underestimated and under-valued factors considered in attempts to address the challenge. It is often in the operating departments that problems that results in turnover first emerged, therefore manager/supervisors are best positioned for early detection and to proactively address these problems. The researcher is further of the opinion that management practices contributes greatly to people’s decisions to stay with or resign from the institution and that if these practices can be addressed greater retention will result. Therefore, even though there is no guaranteed way of making everyone happy, numerous studies proved that in general, there are certain factors that contribute to successful recruitment and retention of employees. These include pay, benefits communication, trust and ethics, support, role clarity, job satisfaction, quality of leadership; empowerment; teamwork; trust and ethics; professional growth and career development; rewards and recognition; job performance; life balance; diversity ; commitment; internal and external equity and good co-worker relations. All the above are factors that either forms of the managers/supervisors direct responsibilities or they are in positions to greatly influence these factors. The researcher iv totally agrees with authors that argue that the manager’s job goes beyond passive reaction and adaptation and it is a manager’s responsibility to make what is desirable first possible, than actual. Except for the obvious financial costs resulting from turnover there are also hidden costs for the organisation which are known as the consequences of turnover and will include amongst other, productivity losses for the organisation, negative impact on the quality of customer service, the negative impact on the morale of the remaining employees and the disruption of the social and communication network within the organisation. Through this study the researcher wants to examine and gain more knowledge on the impact of management practices on staff retention in the Gauteng Provincial Legislature and to come up with suggestions as to how managers can change or better their conduct to contribute to staff retention in the institution
MM - P&DM
Keywords: Staff retention; Gauteng Provincial Legislature